The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1088/1674-1056/21/7/078102
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a static magnetic field on the microwave absorption of hydrogen plasma in carbon nanotubes: a numerical study

Abstract: We theoretically investigate the microwave absorption properties of hydrogen plasma in iron-catalyzed highpressure disproportionation-grown carbon nanotubes under an external static magnetic field in the frequency range 0.3 GHz to 30 GHz, using the Maxwell equations in conjunction with a general expression for the effective complex permittivity of magnetized plasma known as the Appleton-Hartree formula. The effects of the external static magnetic field intensity and the incident microwave propagation direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…There has been a growing interest in the field of carbon nanotubes [1][2][3][4][5][6][7][8][9][10][11][12][13][14] since they were discovered by Iijima, [15] because of their unique properties and great potential applications. Their most advanced applications include nanoelectronics, hydrogen storage, field-emitters, biological and chemical gas sensors, medicine, nanomaterials, etc.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a growing interest in the field of carbon nanotubes [1][2][3][4][5][6][7][8][9][10][11][12][13][14] since they were discovered by Iijima, [15] because of their unique properties and great potential applications. Their most advanced applications include nanoelectronics, hydrogen storage, field-emitters, biological and chemical gas sensors, medicine, nanomaterials, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, one-dimensional (1D) materials have been widely used as microwave absorbers owing to their large specific areas, high aspect ratios, and strong shape effects. [15][16][17][18][19][20] Shen et al [21] investigated the microwave absorption of the nanocomposite BaFe 12 O 19 /Ni 0.5 Zn 0.5 Fe 2 O 4 microfibers. Their results showed that when the specimen thickness is 3 mm, the minimum reflection loss (RL) reaches −35.5 dB at 12.4 GHz, with a wide absorption bandwidth (RL < −20 dB) from 9.1 to 15.7 GHz.…”
Section: Introductionmentioning
confidence: 99%